2009
DOI: 10.1007/s10620-009-0911-4
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Evaluating the Diagnostic Yield of Video Capsule Endoscopy Followed by Directed Double-Balloon Enteroscopy in Patients with Obscure Gastrointestinal Bleeding

Abstract: Capsule endoscopy followed by directed double-balloon enteroscopy is a good strategy for investigating the causes of obscure GI bleeding and especially in confirming indeterminate and negative findings from VCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
0
22
2
3
Order By: Relevance
“…CE enables direct visualisation of the small bowel mucosa and has a high sensitivity for detecting flat lesions, such as angiodysplasias, ulcers and arteriovenous malformations which are not easily detectable on radiological modalities [15] . The reported diagnostic yield in literature ranges from 58.4% to 86.8% [9,14,[16][17][18][19][20][21] . The wide range is attributable to different definitions of a positive finding on CE.…”
Section: Capsule Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…CE enables direct visualisation of the small bowel mucosa and has a high sensitivity for detecting flat lesions, such as angiodysplasias, ulcers and arteriovenous malformations which are not easily detectable on radiological modalities [15] . The reported diagnostic yield in literature ranges from 58.4% to 86.8% [9,14,[16][17][18][19][20][21] . The wide range is attributable to different definitions of a positive finding on CE.…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…The targeted approach is also useful in confirming indeterminate findings from CE. Hence, it is strongly suggested that CE is the initial screening modality in OGIB and that these two investigations should be viewed as complementary [20,64] . Not surprisingly, when compared with PE, a controlled prospective trial on patients with suspected small bowel bleeding, confirmed that anterograde DBE is significantly superior to PE in regards to the detection of pathological lesions (63% vs 44%) and the length of small bowel visualised (230 cm vs 80 cm) [65] .…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…Two recent meta-analyses of studies comparing VCE and DBE have demonstrated comparable diagnostic yields [1,2] . Few studies, however, compared the individual abnormalities detected at VCE with those subsequently confirmed at DBE [9] . We propose to evaluate the test characteristics of VCE for each type of lesion by comparing the results of community based VCE to the findings at follow up DBE for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with positive VCE necessitate endoscopic interventions for effective treatment and DBE has been shown to provide significant aid in patients with small bowel lesions or those who are at high risk for re-bleeding despite a non-diagnostic VCE (25,35). In a meta-analysis of seven studies, the diagnostic yield for DBE after negative VCE for OGIB was 27.5% (95% CI, 16.7-37.8%) (12), while VCE followed by DBE has been established as an effective strategy for investigating OGIB and particularly to confirm a negative VCE examination (53). Hence, DBE does not compete to VCE; it has a rather complementary role.…”
Section: Impact On Subsequent Therapeutic Strategies and Clinical Outmentioning
confidence: 99%